Inborn errors of immunity (primary immunodeficiencies) - Vy H. D. Kim; Julia E. M. Upton; Beata Derfalvi; Kyla J. Hildebrand; Christine McCusker (Allergy, Asthma & Clinical Immunology)
Abstract Primary immunodeficiencies (PID), now often referred to as inborn errors of immunity (IEI), are a large heterogeneous group of disorders that result from deficiencies in immune system development and/or function. IEIs can be broadly classified as disorders of adaptive immunity (e.g., combined or humoral immunodeficiencies) or of innate immunity (e.g., phagocyte and complement disorders). Although the clinical manifestations of IEIs are highly variable, traditionally many disorders involve an increased susceptibility to infection. Research in recent years has underscored how IEI can present with features other than infection such as: severe atopy, autoimmunity, autoinflammation, lymphoproliferation, and/or malignancy resulting from immune dysregulation. Early consultation with a clinical immunologist is essential, as timely diagnosis and treatment are imperative for preventing significant disease-associated morbidity and mortality. The treatment of IEIs is complex and generally requires both supportive and definitive strategies, including but not limited to, immunoglobulin replacement therapy, antibiotic prophylaxis, immune response modifiers, and hematopoietic stem cell transplantation. This article provides an overview of the major categories of IEIs and strategies for the appropriate diagnosis and management of these disorders.